Pembuatan eco-enzym sebagai alternatif pengolahan limbah rumah tangga bagi masyarakat Desa Sraten - Izzati, Nusaibah; Sarii, Rika Purnama; Rahmadani, Laela Ardiana; Firmansyah, Mohamad Novan; Susapti, Peni (Tintamas: Jurnal Pengabdian Indonesia Emas, 2024)
An environmental issue that Indonesia still needs to handle is waste. The amount of collected waste increases along with the increase in population. Around 60% of waste falls into organic waste, which will cause methane gas and lead to greenhouse emissions if not processed correctly. Converting organic waste into eco enzymes is a way to protect the environment. Therefore, we will socialize about the dangers of waste to society so that waste can be processed properly, and it will be even more profitable if valuable products can be obtained. This research used the Participatory Action Research (PAR) method, where the society was the participant and the KKN students were the researchers. Eco enzyme products can be categorized as successful after a three-month fermentation process if the liquid changes colour to brown and mould grows on the surface.